Impact of partial root-zone drying on growth, yield and quality of tomatoes produced in green house condition - Hakim, Abdul; Qinyan, Zhu; Khatoon, Mohfeza; Gullo, Safawo (Advances in Horticultural Science, 2018)
Water resources are limited for irrigation worldwide especially for the arid and semi-arid regions; therefore, there is an urgent need to reassess an alternative technique for conventional irrigation. Partial root-zone drying (PRD) is considered a new water-saving irrigation technique which has been tested for some crop species. The PRD technique simply requires wetting half of the rooting zone and leaving the other half dry, thereby utilizing reduced amount of irrigation water. The wetted and dry sides are interchanged in the subsequent irrigations. The focus of this article is to evaluate the effect of PRD on growth, yield and quality of tomatoes as compared to conventional irrigation. To evaluate the effect of PRD, a greenhouse experiment was conducted where two irrigation treatments were tested during a 160-day growing period: (1) control treatment where drip irrigation was applied to both sides of the plants; (2) PRD treatment in which half of the irrigation water in drip irrigation was given alternately only to one side of the root system with each irrigation. PRD treatment had 15% and 7% decreases in shoot fresh weight and leaf area of plant, respectively; however, PRD had 20% higher fruit per cluster and 18% increase in fruit production in comparison to the control treatment. No significant difference was detected on fruit size between PRD treated plants and control plants. But, fruits from PRD treated plant exhibited better appearance, higher lycopene content, firmness, total soluble solid (TSS), and TSS/titratable acidity (TA) ratio than control ones. Fruit from control treatment contained higher chlorophyll content than fruit from the PRD treatment. Postharvest storage results indicated that higher percentage of rot and chilling injury were observed in control fruits than PRD treated fruits. The results of this study indicated that PRD is a promising water saving irrigation technique which is able to produce higher yield and better quality tomatoes than conventional drip irrigation.